2017
DOI: 10.5152/turkjsurg.2017.3448
|View full text |Cite
|
Sign up to set email alerts
|

Publication rates of abstracts presented at the annual congress of the Turkish Society of Colorectal Surgery (years 2003-2011)

Abstract: INTRODUCTIONA scientific congress is an environment in which physicians with the same specialty and other health staff participate in, the results of which is shared as abstracts, and in which ideas are exchanged with one another. The abstracts presented in scientific congresses (oral/poster) are evaluated by the commissions that are assigned by the congress scientific committee during the preparation period of the congress and it is decided if the studies will be accepted in the congress or not.The publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 5 publications
3
9
0
3
Order By: Relevance
“…In order to optimize the likelihood that abstracts reach full-text publication, other medical societies have suggested being more selective in the acceptance of abstracts for presentation at their annual meetings by paying greater attention to quality measures such as sample size and data analysis, study design, outcomes, and instrument validity ( Sawatsky et al, 2015 ; Meral et al, 2017 ). Involvement of multiple institutions, use of validated instruments and appropriate statistical analysis, prospective study design, and reporting new findings (as opposed to confirmatory investigations) are factors that indicate eventual publication ( Gilbert and Pitkin, 2004 ; Sawatsky et al, 2015 ; Meral et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to optimize the likelihood that abstracts reach full-text publication, other medical societies have suggested being more selective in the acceptance of abstracts for presentation at their annual meetings by paying greater attention to quality measures such as sample size and data analysis, study design, outcomes, and instrument validity ( Sawatsky et al, 2015 ; Meral et al, 2017 ). Involvement of multiple institutions, use of validated instruments and appropriate statistical analysis, prospective study design, and reporting new findings (as opposed to confirmatory investigations) are factors that indicate eventual publication ( Gilbert and Pitkin, 2004 ; Sawatsky et al, 2015 ; Meral et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The only two published studies appraising meetings in the field of coloproctology (none of which compares two colorectal societies) refer to the United Kingdom society, with a conversion rate of 24.3% when evaluating a single edition of the congress (2001), and the Turkish society, with a conversion rate of 22.6% regarding the evaluated abstracts from four editions of the congress, held between 2003 and 2011. 14,15 In the current analysis, of the 524 abstracts presented in the American Congress, 127 (24.2%) were published, which is a rate 2.5 times higher than that of the Brazilian Congress (35/330; 10.6%).. These data show that much of the scientific content produced in coloproctology is restricted, never reaching the international scientific community.…”
Section: Discussionmentioning
confidence: 63%
“…The only two published studies appraising meetings in the field of coloproctology (none of which compares two colorectal societies) refer to the United Kingdom society, with a conversion rate of 24.3% when evaluating a single edition of the congress (2001), and the Turkish society, with a conversion rate of 22.6% regarding the evaluated abstracts from four editions of the congress, held between 2003 and 2011. 14 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 It is possible that as knowledge generation tends to be poor in some Latin American countries, the selection criteria might be lower than international standards, which may lead to a lower chance of publication afterward. 12,16 We also found that the proportion of publication among abstracts authored by most or all authors from Peruvian institutions was half of the proportion of publication among abstracts authored by a higher percentage of international collaborators. This result is in accordance with that of previous research, which describes an increase in Peruvian scientific production from 2000 to 2009, probably related to the existence of international collaborating networks and foreign authors dealing with publication processes.…”
mentioning
confidence: 56%